Investigative journalism - Singh, Sanoj (Random Publications LLP, 2022)
Investigative journalism is a form of journalism in which reporters deeply investigate a single topic of interest, such as serious crimes, political corruption, or corporate wrongdoing. An investigative journalist may spend months or years researching and preparing a report. Practitioners sometimes use the words "watchdog reporting" or "accountability reporting." Underneath the umbrella term of investigative journalism is interpretive reporting, which is a type of investigative journalism that evaluates the consequences of certain events or actions. Keep in mind, however, that investigative journalism is not leak journalism, which is when a reporter releases sensitive documents to the public without any further research into the documents. Journalism ethics and standards comprise principles of ethics and good practices as applicable to the specific challenges faced by professional journalists. Historically and currently, this subset of media ethics journalism is widely known to journalists as their professional "code of ethics" or "canons of journalism." The basic codes and canons commonly appear in statements drafted by both professional journalism associations and individual print, broadcast, and online news organizations. Investigative journalists use a variety of resources to learn more about the topic they are investigating. Reporters will use information from interviews. public records, legal and tax reports and other federal resources. Journalists use standard undercover work when there isn't enough information in databases or when sources aren't willing to come forward. Usually a combination of these different methods is used to build a strong case. This book explores the history, theory and practice of investigative journalism around the world.